AB0679 Comparison of Two Different Ethnic Groups of as Patients. (10th June 2014) - Delle Sedie, A.; Riente, L.; Bandinelli, F.; Bi, Y.; Xu, Q.; Cao, Y.; Yuan, Y.; Zuo, F.; Gao, Y.; Matucci Cerinic, M.; Bombardieri, S.; Xiao, C.
Abstract : Background: Ankylosing spondylitis (AS) represents a world-wide diffused disease with a strong genetic factor. How subjects cope with their disease may depend on many different causes, such as education, general life-style, physical activity, etc. Few studies have reported a comparison between different parameters in two different ethnic populations. Objectives: To investigate the possible differences regarding the main findings between two groups of AS patients native to Italy and China. Methods: We examined patients affected by AS in two different areas: Italy (Pisa and Florence) and China (Guangzhou). All of them were asked to complete questionnaires on disease activity (BASDAI), function (BASFI), global assessment (BASGI), quality of life (SpA-HAQ), fatigue (FACIT and BASDAI fatigue item), pain (VAS-pain), and probability of anxiety and depression (HADS-A and HADS-D). Therapy was registered for all of the patients. The Student t -test was used to analyse the differences between the two groups. Results: Sixty patients were examined. The two populations were slightly different in the M/F ratio (18/10 in Italy and 25/7 in China) and mostly in the mean age (53±13.68 and 29±9.27 years in the two groups, respectively). No differences were found between the two groups regarding all of the questionnaires studied (Table 1 ). A trend to significance was found for HADS-A (higher in Italian patients). While a difference was shown in the NSAIDs intake (higher in China), no significant difference was found for anti-TNF-a therapy in the two groups. Conclusions: Even if the two group are not completely comparable given the different mean age and sex ratio, the expression of the disease seems to be similar, as well as all the parameters studied. A trend toward significance was found for anxiety, showing a slightly higher probability in Italian patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3657